Elder Mistreatment Victims during the COVID-19 Pandemic: Administrative Data from San Francisco Adult Protective Services - Liu, Pi-Ju (Journal of family violence, 2022)
This study examined elder mistreatment victims’ experiences at the beginning of the COVID-19 pandemic, focusing on their COVID-19 awareness and unmet needs. San Francisco Adult Protective Services (APS) caseworkers conducted phone interviews with clients or collaterals (client’s family, trusted other, or service provider) to inquire about clients’ awareness of COVID-19 and unmet needs. Nine-hundred-and-thirty-four (71%) of 1,313 APS’ past clients or their collaterals were interviewed, with 741 (79%) responding positively to COVID-19-awareness questions, and 697 (75%) having no unmet needs. Binary logistic regression with Firth adjusted maximum likelihood estimation method revealed that older persons (p < .05), self-neglectors (p < .05), and victims of neglect (p < .05) were less aware of COVID-19. Unmet needs varied by mistreatment type. Victims of isolation were more likely to have medical needs (p < .05), while victims of emotional abuse were more likely to report loneliness (p < .001). Case notes reflected clients who were well-prepared for the pandemic, versus those who required additional assistance to follow preventative measures of the COVID-19 pandemic to stay home. Although the majority of San Francisco APS’ past clients experienced no unmet needs at the beginning of the COVID-19 pandemic, the prolonged length and intensity of the pandemic could have exacerbated this vulnerable group’s situation. Collaboration between service providers is key in assisting victims experiencing unmet needs to live safely in a public health crisis, especially underserved victims of specific ethnic backgrounds.